Monochorionic monoamniotic twins- a five year review. (18th April 2012) - Donnelly, JC; Murray, AM; Burke, N; Breathnach, FM; Geary, MP; Barry, C; Malone, FD
Abstract : Aim: To identify the incidence of monochorionic monoamniotic (MCMA) twins over a 5 year period in a tertiary referral centre and to assess the perinatal outcome this group. Methods: A retrospective search of ultrasound database of both electronic and paper records was performed from October 2006-October 2011. All pregnancies >12 weeks were included. Chorionicity was confirmed by histological review of placentae. Results: 359 monochorionic pregnancies were identified, 6.4% (24) were MCMA. There were 2 TRAP sequences, 2 conjoined twin pairs, 2 MCMA pairs within triplet pregnancies, 2 twin pairs with congenital anomalies. 14/24 (61%) had USS evidence of cord entanglement. Excluding conjoined twins, TRAP and triplets, there were 18 simple MCMA pairs with a loss rate after 12 weeks of 14/36 (38%), excluding congenital anomalies this was 31%. Double demise was more common. After 20 weeks, there were 4/24 IUD (15%) and after 24 weeks there were no IUDs. Maternal age range was 17-34 years, ( mean 27). The mean infant birthweight was 1824g. Length of stay in NICU ranged from 3-18 days ( mean 8.3). The only neonatal death was an infant with a prenatally diagnosed congenital anomaly. The mean gestational age at delivery was 32 weeks for the liveborn twin pairs, with a 100% caesarean section rate. Conclusion: Perinatal mortality is mainly a consequence of conjoined twins, TRAP, congenital anomalies and miscarriage less than 20 weeks gestation. Perinatal survival in MCMA twins managed by close ultrasound surveillance and elective delivery at 32-34 weeks is high.